Neoadjuvant immunochemotherapy improves clinical outcomes of patients with esophageal cancer by mediating anti-tumor immunity of CD8+ T (Tc1) and CD16+ NK cells - He, Yunlong; Yang, Depeng; Lin, Xiaoyu; Zhang, Jinfeng; Cheng, Rui; Cao, Liangyu; Yang, Lijun; Zhang, Mengmeng; Shi, Xinyue; Jin, Xiyun; Sun, Handi; Sun, Haoxiu; et al. (Frontiers in Immunology, 2024)
Background Esophageal cancer (ESCA) is one of the most common tumors in the world, and treatment using neoadjuvant therapy (NT) based on radiotherapy and/or chemotherapy has still unsatisfactory results. Neoadjuvant immunochemotherapy (NICT) has also become an effective treatment strategy nowadays. However, its impact on the tumor microenvironment (TME) and regulatory mechanisms on T cells and NK cells needs to be further elucidated. Methods A total of 279 cases of ESCA who underwent surgery alone [non-neoadjuvant therapy (NONE)], neoadjuvant chemotherapy (NCT), and NICT were collected, and their therapeutic effect and survival period were compared. Further, RNA sequencing combined with biological information was used to analyze the expression of immune-related genes. Immunohistochemistry, immunofluorescence, and quantitative real-time PCR (qRT-PCR) were used to verify the activation and infiltration status of CD8+ T and CD16+ NK cells, as well as the function and regulatory pathway of killing tumor cells. Results Patients with ESCA in the NICT group showed better clinical response, median survival, and 2-year survival rates (p < 0.05) compared with the NCT group. Our RNA sequencing data revealed that NICT could promote the expression of immune-related genes. The infiltration and activation of immune cells centered with CD8+ T cells were significantly enhanced. CD8+ T cells activated by PD-1 inhibitors secreted more IFN-γ and cytotoxic effector factor cells through the transcription factor of EOMES and TBX21. At the same time, activated CD8+ T cells mediated the CD16+ NK cell activation and secreted more IFN-γ to kill ESCA cells. In addition, the immunofluorescence co-staining results showed that more CD276+ tumor cells and CD16+ NK cells were existed in pre-NCT and pre-NICT group. However, CD276+ tumor cells were reduced significantly in the post-NICT group, while they still appeared in the post-NCT group, which means that CD16+ NK cells can recognize and kill CD276+ tumor cells after immune checkpoint blocker (ICB) treatment. Conclusion NICT can improve the therapeutic effect and survival period of resectable ESCA patients. NICT could promote the expression of immune-related genes and activate CD8+ T and CD16+ NK cells to secrete more IFN-γ to kill ESCA cells. It provides a theoretical basis and clinical evidence for its potential as an NT strategy in ESCA.